TOPONIMI SEBAGAI PELESTARI BUDAYA LOKAL DI KELURAHAN BENER, KECAMATAN TEGALREJO, KOTA YOGYAKARTA - Sekarsih, Fitria Nuraini; Arsanti, Vidyana (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Universitas Negeri Malang, 2020)
Abstrak:Â Kelurahan Bener merupakan salah satu perkampungan yang berkembang di sekitar Kota Yogyakarta. Penamaan Bener tidak dapat lepas dari berdirinya kerajaan Ngayogyakarta Hadiningrat yang dipimpin oleh Hamengku Buwono (HB) 1. Pembukaan hutan untuk mencari sumber mata air kebutuhan kraton menjadi latar belakang penamaan Bener dan nama daerah di sekitarnya. Metode yang digunakan untuk mencari latar belakang penamaan tersebut adalah snowballing sampling dengan mencari informasi dari tokoh sesepuh Bener. Melalui wawancara ini, dilakukan pemetaan partisipatori untuk menelusur peristiwa secara berurutan. Cerita dari para narasumber disusun menjadi cerita sejarah yang berurutan dan logis. Melalui proses ini, penggunaan peta mempermudah narasumber untuk menandai beberapa lokasi penting. Dari peristiwa tersebut, muncullah 18 nama kampung, dusun, desa, bahkan kecamatan, termasuk Bener itu sendiri. Tokoh yang muncul dari peristiwa tersebut adalah sosok Kyai Bener yang ternyata tidak banyak diketahui warga Kelurahan Bener. Survey singkat menunjukkan sedikit saja yang mengetahuinya, selebihnya masyarakat tidak tahu siapa itu Kiayi Bener. Oleh sebab itu, toponimi dapat dijadikan sebagai media pelestari budaya lokal. Melalui sebuah nama, cerita asal mula sebuah daerah dapat dijadikan warisan budaya yang patut untuk dilestarikan khususnya di Kelurahan Bener, Kecamatan Tegalrejo, Kota Yogyakarta.Abstract: Bener Village is one of the villages that has developed around the city of Yogyakarta. The naming of Bener cannot be separated from the establishment of the Ngayogyakarta Hadiningrat kingdom which was led by Hamengku Buwono (HB) 1. Forest clearing to find water sources for the palace needs became the background for the naming of Bener and the names of the surrounding areas. The method used to find the background of the naming is snowballing sampling by seeking information from the elder figures of Bener. Through these interviews, participatory mapping was carried out to track events sequentially. The stories of the speakers are organized into sequential and logical historical stories. Through this process, the use of maps makes it easier for informants to mark several important locations. From this incident, 18 names emerged from the village, hamlet, village, even the district, including Bener itself. The figure who emerged from the incident was the figure of Kyai Bener, who was not widely known by the residents of Bener Village. A short survey shows that few people know about it, the rest people don't know who Kiayi Bener is. Therefore, toponymy can be used as a medium for preserving local culture. Through a name, the story of the origin of an area can be used as a cultural heritage that deserves to be preserved, especially in Bener Village, Tegalrejo District, Yogyakarta City. toponymy can be used as a medium for preserving local culture. Through a name, the story of the origin of an area can be used as a cultural heritage that deserves to be preserved, especially in Bener Village, Tegalrejo District, Yogyakarta City. toponymy can be used as a medium for preserving local culture. Through a name, the story of the origin of an area can be used as a cultural heritage that deserves to be preserved, especially in Bener Village, Tegalrejo District, Yogyakarta City.Â